Fabrication and evaluation of herbal beads to slow cell ageing - Dhasmana, Archna; Malik, Sumira; Sharma, Amit Kumar; Ranjan, Anuj; Chauhan, Abhishek; Harakeh, Steve; Al-Raddadi, Rajaa M.; Almashjary, Majed N.; Bawazir, Waleed Mohammed S.; Haque, Shafiul (Frontiers in Bioengineering and Biotechnology, 2022)
An aging sign of premature cell death, skin dullness, or change in morphology. Clinically to prevent or delay cell aging, different cosmetics and therapies are available commercially. Besides that, herbal products such as Aloe-vera, curcumin, Vitamin C enriched natural antioxidant, and anti-inflammatory bio-molecules are potential sources to prevent or delay aging. Eggshell membrane (ESM) is also a rich source of collagen; GAGs play an essential role in healing and preventing aging. Although these all products have significant anti-aging properties and the ability to regenerate healthy cells, there is a need for a therapeutic process for prolonged effect without reducing their efficiency. Therefore, herbal component encapsulated beads are designed to overcome this problem for prolonged effects and have a long shelf life. Bio-polymeric beads encapsulated anti-aging molecules have been fabricated and evaluated as a natural anti-aging product. 3D crosslinked polymeric network provides a matrix for the entrapment of bio-molecules and prolonged controlled release of molecules for an anti-inflammatory, anti-oxidative and antimicrobial activity. Conclusively, herbal beads are the most effective and feasible natural remedy or therapeutic system for aging treatment and environmentally friendly products.